Neo Banks: Assessing Risk Factors Contributing to their Failures - Umair Hussain; Sohaib Uz Zaman (Indus Journal of Social Sciences, 2025)
The current study evaluates key risks which result in Neo Banks’ failure within emerging economies such as Pakistan. This research examines economic along with political elements and regulatory requirements and compliance risks and their synergy toward the continued operation of these online-only banks. Data was collected through structured questionnaires to carry out a quantitative research design. The survey collected responses from 225 people including banking experts combined with fintech professionals along with SME business owners and personal consumers. The association between risk factors and Neo Bank failure was analyzed using descriptive statistics in conjunction with correlation and regression methods which were computed on SPSS. The research data showed that risk association strongly matched (r = 0.682, p = 0.000) with failure causes. The results show risk association produces 46.5% variance in failure causes according to regression analysis (R² = 0.465). Effective risk management measures become necessary for Neo Banks because economic instability and political uncertainties along with regulatory restrictions and compliance issues continue to lead to their failure. As these findings demonstrate the implementation of strong risk mitigation practices including enhanced regulatory compliance better cyber security measures and revenue stream diversity has become crucial to Neo Banks’ operational success. The regulatory authorities and financial establishments should establish regulatory systems to promote Fintech innovations while maintaining banking safety. New research provides statistical evidence which enriches knowledge about Neo Banks’ difficulties in emerging markets so it complements existing works on fintech sustainability. Digital banking becomes more sustainable through the valuable recommendations outlined in the research which address regulators’ needs and investors’ demands and fintech entrepreneurs’ operations.